2018
DOI: 10.1186/s12891-018-2216-2
|View full text |Cite
|
Sign up to set email alerts
|

A new anatomic locking plate for the treatment of posterolateral tibial plateau fractures

Abstract: BackgroundPosterolateral tibial plateau fractures have become more common, and their treatment is of great importance to knee function. Additionally, there is no available literature detailing specialized anatomic locking plate for tibial plateau fractures. Therefore, the aim of the study was to evaluate the safety and clinical efficacy of an innovative anatomic locking plate for treatment of posterolateral tibial plateau fractures.MethodsBetween March 2014 and January 2016, 12 patients with posterolateral tib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Intra-articular fractures need proper anatomic reduction with rigid fixation for a painless bony union to occur. 12,13 The average time to union which was determined radiologically was about 4.4 months. 2 of our patients had delayed union taking 10 and 11 months respectively for union.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-articular fractures need proper anatomic reduction with rigid fixation for a painless bony union to occur. 12,13 The average time to union which was determined radiologically was about 4.4 months. 2 of our patients had delayed union taking 10 and 11 months respectively for union.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, 3D printing technology has been widely used in the eld of orthopaedic trauma, and this technology can transform two-dimensional images into solid models [15].3D images allow for more accurate pre-operative planning, simulation of surgery, and other operations, leading to a complete and personalized surgical plan [16,17].By creating a 3D model, the surgeon has a clearer understanding of the patient's fracture, which provides a basis for the selection and placement of xation and increases the likelihood of fracture reduction [18].Xie and Shen compared 3D printing with incisional internal xation in the treatment of tibial plateau fractures, and showed that 3D printing shortened operative time and fracture site healing time, and reduced operative bleeding [19,20].Ren, Jian et al tested a common plate and a new anatomically locked plate by 3D printing technology, respectively, and the newly designed xation material is stable and reliable, and more suitable for clinical application [21,22].However, there are no reports on the use of 3D printed fracture external repositioning models with preoperative placement of rigid markers.…”
Section: Discussionmentioning
confidence: 99%
“…The wide proximal part can achieve excellent wrapping of the posteromedial condyle. Four proximal row screws paralleled with the plateau could buttress powerfully, having a “raft effect,” 26 which provides firm strength holding the articular surface. Not only an effective buttress can be achieved, but also compression fixation of large fragments.…”
Section: Discussionmentioning
confidence: 99%